The accuracy of existing prehospital triage tools for injured children in England: an analysis using emergency department data. Issue 5 (8th April 2014) - Ardolino, Antonella; Cheung, C Ronny; Lawrence, Thomas; Bouamra, Omar; Lecky, Fiona; Berry, Kathleen; Lyttle, Mark; Roland, Damian; Koralage, Nadeeja; Issa, Shabara; Chaudhary, Adeel; Maconochie, Ian; et al.
Abstract : Objective: To investigate the performance characteristics in children with moderate and minor injuries of prehospital paediatric triage tools currently in use in England for identifying seriously injured children. Methods: Eight prehospital paediatric triage tools were identified from literature review and a survey of the lead trauma clinicians across the 10 English strategic health authorities. Retrospective clinical data from 2934 patient records collected by four emergency departments were used to analyse each tool. A target sensitivity of >95% and specificity of 50–75% was set based on the literature. Results: Three tools (East Midlands, North West and Northern) demonstrated acceptable sensitivity (all 100%). The other five tools fell below the target sensitivity of >95%. All eight tools had acceptable specificity (with results between 79% and 99%). Conclusions: Three tools (East Midlands, North West and Northern) demonstrated acceptable over- and under-triage rates in this population of minor and moderately injured children. All tools reached recommended standards for over-triage, but the majority favoured under-triage.